PEMANFAATAAN BENTENG VAN DER WIJCK GOMBONG KABUPATEN KEBUMEN JAWA TENGAH SEBAGAI OBJEK WISATA DAN SUMBER BELAJAR SEJARAH - Faidatunnisa Isnaniyah (Khazanah Pendidikan, 2016)
This study entitled The Utilization of Van DerWijck Castle in Gombong, Kebumen Regency, Central Java as Tourist Attraction and Source of Learning History. The aims of this study are (1) to examine the utilization of Van Der Wijck Castle as tourist attraction, (2) the utilization of Van Der Wijck Castle as source of learning history, (3) the factors supporting and inhibiting the utilization of Van Der Wijck Castle in Gombong as tourist attraction and source of learning history. This study used qualitative approach. Data collection was performed by the following steps: (1) observation, (2) interview, (3) documentation. The main informants were manager and visitors of Van Der Wijck Castle tourist attraction. The analysis technique was Miles and Huberman qualitative data analysis consisting of data reduction, data display/presentation, and drawing conclusion or verification. The result of this study showed that Van Der Wijck Castle in Gombong was a Dutch colonial heritage building located in Sidayu Village, Gombong District, Kebumen Regency. The function of the castle has changed from Ducth Company station into a tourist attraction and source of learning history. Since 2000, Van Der Wijck Castle was used as a tourist attraction. The castle was used as source of learning history for students and society by taking the values that existed in the castle. The strategic location and the presence of adequate facility were supporting factors to Van Der Wijck Castle used as a tourist attraction and source of learning history. The inhibiting factor was the lack of public awareness of the tourism activities. Keywords: Van Der Wijck, historical tourism, source of learning history